Maximum specific cycle net-work based performance analyses and optimizations of thermodynamic gas power cycles - Di He; Yusong Yu; Chaojun Wang; Boshu He (Case Studies in Thermal Engineering, 2022)
A gas power engine is expected to output work or power through cycle, and the work is expected as much as possible in terms of viewpoints of a unit fuel, a unit volume of an engine, or a unit displaced volume of an engine. Evaluation of gas power engines with thermal efficiency, especially for reciprocating engines, instead of specific cycle net-work (SCNW) might mislead the engineering applications. Based on the generalized property diagrams for the gas power cycles proposed by the authors, an ideal Otto cycle and an ideal Miller-Diesel cycle are analyzed for they are relatively simple gas power cycles. The optimum compression ratio (or the pressure ratio) for the maximum SCNW or the maximum mean effective pressure (MEP) is analyzed and optimized. Detailed analyses of a four-stroke Otto engine operating at three compression ratios show the mass of working fluid is saved 0.45–0.49% operating at the maximum SCNW condition, even though the thermal efficiency is not the highest. The ideal Otto and the ideal Miller-Diesel cycles, and also other gas power cycles, are concluded that the operation under the condition of maximum SCNW or maximum MEP, instead of that of higher efficiency, is more reasonable and economic.